2018
DOI: 10.1186/s12884-018-1824-z
|View full text |Cite
|
Sign up to set email alerts
|

Screening for congenital fetal anomalies in low risk pregnancy: the Kenyatta National Hospital experience

Abstract: BackgroundCongenital malformations contribute significantly to the disease burden among children globally. A study conducted in Kenya on understanding the burden of surgical congenital anomalies, highlights the need for Kenyan health systems to go beyond the medical dimensions of illness. This could be achieved by linking knowledge of the severe congenital anomalies (CAs) and their impact of varying disability to the delivery of local health services and public health program planning. Subsequently, early dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…This delay in antenatal diagnosis of congenital malformations is also reported in other studies covering developing countries with, for example, a median gestational age of 31 weeks in Saudi Arabia and 32 weeks in Kenya [31,32].…”
Section: Discussionsupporting
confidence: 79%
“…This delay in antenatal diagnosis of congenital malformations is also reported in other studies covering developing countries with, for example, a median gestational age of 31 weeks in Saudi Arabia and 32 weeks in Kenya [31,32].…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of CAs seems to be varied; Sunitha et al (2017) suggested that eleven percent were pregnant women carrying fetuses with CAs. Onyambu and Tharamba (2018) showed that the prevalence of CAs through routine U/S was 3%. Ukweh et al (2019) concluded that anomaly prevalence is 1.67%.…”
Section: Asymptomaticmentioning
confidence: 99%
“…Most of the time ultrasound (USG) screening provides reassurance to the couples, however, less than 5% of the scans revealed otherwise [ 4 , 5 , 17 19 ] CNS anomalies accounts for the highest percentage of prenatally detected deformities among all organ systems [ 3 , 4 , 11 , 13 , 20 , 21 ], with an incidence of 2-10 per 1000 live births [ 22 – 25 ]. With the advancement in imaging technologies offering a better resolution of the fetal cerebral structures and enhancement in the skill of sonographers, the detection rate was expected to rise [ 14 , 16 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%